PELATIHAN PENGELOLAAN KAS KECIL MENGGUNAKAN APLIKASI JETTY CASH - Sari, Tridarma Rosmala; Sabrina, Hany; Andini, Novilya M.; Ambarwati, Putri (Universitas Teknokrat Indonesia, 2024)
Understanding financial management, especially cash management, is very important because cash is very easy to misuse. Based on the results of interviews with teachers majoring in accounting at SMAN 1 Tanjung Karang, data was obtained that class petty cash in daily money management. Petty Cash training using the Jetty Cash application broadens the training participants' insight into the concept of financial management more effectively and efficiently. This can be seen from the active participation of students, and their enthusiasm in asking questions and discussing.